2005
DOI: 10.1073/pnas.0508778102
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal viability and diminished stress tolerance in mutants lacking the signal recognition particle pathway or YidC2

Abstract: The signal recognition particle (SRP)-translocation pathway is conserved in all three domains of life and delivers membrane and secretory proteins to the cytoplasmic membrane or endoplasmic reticulum. We determined the requirement in the cariogenic oral pathogen Streptocococcus mutans of the three universally conserved elements of the SRP pathway: Ffh͞SRP54, scRNA, and FtsY͞SR␣. Previously, we reported that insertional interruption of S. mutans ffh was not lethal, but resulted in acid sensitivity. To test whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 69 publications
8
148
0
Order By: Relevance
“…Similar to most Gram-positive bacteria, GAS encode two YidC proteins, YidC1 and YidC2. While not studied in GAS, YidC1 and YidC2 have been studied in S. mutans, where deletion of yidC1 caused only a minor growth phenotype while deletion of yidC2 resulted in a major stress phenotype similar to an SRP mutant strain (Hasona et al, 2005). Disruption of both yidC2 and components of the SRP pathway gave S. mutans strains that were severely impaired in growth and stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to most Gram-positive bacteria, GAS encode two YidC proteins, YidC1 and YidC2. While not studied in GAS, YidC1 and YidC2 have been studied in S. mutans, where deletion of yidC1 caused only a minor growth phenotype while deletion of yidC2 resulted in a major stress phenotype similar to an SRP mutant strain (Hasona et al, 2005). Disruption of both yidC2 and components of the SRP pathway gave S. mutans strains that were severely impaired in growth and stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…While isogenic 4.5S RNA, ffh and ftsY mutant strains of the cariogenic oral pathogen Streptococcus mutans are viable, they have diminished tolerance to several stresses, including low pH and high salt (Hasona et al, 2005;Kremer et al, 2001). In the absence of stress, growth yield was similar between the parental and SRP mutant S. mutans strains, although the doubling time increased.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial SRP translocation pathway was previously studied in E. coli and B. subtilis and in both cases was found to be essential for cell viability (Keenan et al, 2001;Phillips & Silhavy, 1992). However, proteins of the SRP pathways were unexpectedly shown to be dispensable in S. mutans (Hasona et al, 2005). Further studies revealed that overlapping and compensatory pathways exist in S. mutans and allow the organism to adapt and maintain membrane function in the absence of the SRP (Funes et al, 2009).…”
Section: S Mutans Is the Bacterial Paradigm Of Lactic Acid Bacteria mentioning
confidence: 99%
“…In turn, some signaling pathways could also affect ATP synthesis under stress. In Streptococcus, mutants deficient in the minimally conserved bacterial signal recognition particle (SRP) elements remain viable but are more sensitive to environmental stress because the SRP deficiency decreases ATPase activity and limits the ATP supply [40,41] . It was found that industrial strain grown on high environmental stress have a high ATP demand [42] and increase ATP supply [43] could well facilitate the resistance to stress.…”
Section: Applications Of Atp Manipulationmentioning
confidence: 99%